PREFACIOS DE DINERO, CRÉDITO BANCARIO Y CICLOS ECONÓMICOS HASTA LA 8ª EDICIÓN - , Huerta de Soto, J. (REVISTA PROCESOS DE MERCADO, 2024)
Following the success of the first edition of Dinero, Crédito Bancario y Ciclos Económicos, which sold out rapidly, I am pleased to present the second edition to Spanish-speaking readers. To avoid confusion and facilitate the work of scholars and researchers, the contents, structure and page numbering of the first edition have been maintained in the second, though the book has been thoroughly examined and all misprints detected have been eliminated.